Transformation of Learning through Virtual Reality in Senior High School - Kustandi, Cecep; Ibrahim, Nurdin; Muchtar, Hartati (International Journal of Psychosocial Rehabilitation, 2020)
This qualitative research aims to describe transformation of learning through virtual reality in senior high school. This study has a special purpose that is to present the use of virtual reality as an opportunity to support students in learning process. Data was collected through observation in the class while history subject was conducted during learning process, and the researcher collaborated with two history subject teachers and fifteen students in senior high school grade one and media expert for an interview. The study was conducted in first semester of academic year 2018. This research also organized the literature study to better identify indicators that can account for future valid. The research was in Cendrowski High School, South Jakarta, Indonesia. The results showed virtual reality application-built students’ interaction in the history class, enhanced cognitive skills and also authentic experiences to impact students’ identity. The implication of the use of virtual reality allowed students for new perspective taking and empathy, increases students’ creativity and students’ ability of visualizing difficult models.